Image quality assessment: A case study on ultrasound images of supraspinatus tendon - Gupta, R. (Springer Verlag, 2016)
With the advancement of technologies on visual contents and the rate at which data is being captured, viewed, stored, and shared, the importance of assessment of quality of the contents has major importance. Image quality assessment has remained a topic of research over the last several decades for optical as well as medical images. User oriented image quality assessment is playing a key role in the assessment of visual contents. Studies are conducted to imitate the accuracy of human visual system for assessment of images. This chapter details about the approaches for development of methods for image quality assessment followed by brief introduction on existing image quality assessment methods. Later in the chapter, challenges for validation and development of image quality assessment metric for medical images are briefly discussed followed by the case study for assessment of ultrasound images of supraspinatus tendon. Â© Springer International Publishing Switzerland 2016.